Economic evaluation of doravirine/tenofovir disoproxil fumarate/lamivudine for HIV-1-infected adults in Russia: a cost-minimization and budget impact analysis. (17th November 2022) - Pyadushkina, Elena; Derkach, Elena; Rozenberg, Vladimir; Ugrekhelidze, Dzhumber; Lobodina, Alena; Baxter, Carl; Beyer, Andrew
ABSTRACT: Background: In Russia, before 2022, the list of vital and essential drugs for HIV-infected patients previously untreated with antiretroviral drugs included the fixed-dose combination rilpivirine/tenofovir disoproxil fumarate/emtricitabine (RPV/TDF/FTC) but not doravirine/tenofovir disoproxil fumarate/lamivudine (DOR/TDF/3TC). Methods: An indirect comparison of the efficacy of DOR/TDF/3TC and RPV/TDF/FTC defined by virologic suppression (HIV-1 RNA of <50 copies/mL at week 48) was made. The per-patient drug costs over 1 year were compared in a cost-minimization analysis. A budget impact analysis considered the costs to the healthcare system of including DOR/TDF/3TC as a treatment option for eligible patients in Russia over a 3-year time horizon. Results: The indirect treatment comparison of DOR/TDF/3TC and RPV/TDF/FTC in treatment-naïve patients with baseline HIV-1 RNA 100, 000 copies/ml or less showed no statistically significant difference (RR 0.914, 95% CI 0.833–1.003). In the cost-minimization analysis, the per-patient cost of one year of treatment with RPV/TDF/FTC and DOR/TDF/3TC was, respectively, ₽320, 975 and ₽151, 192, for a saving of ₽169, 783. In the budget impact analysis, the adoption of DOR/TDF/3TC into clinical practice is expected to reduce drug costs by ₽333 million (23.8%) in year 3. Conclusions: Fixed-dose combination DOR/TDF/3TC is equally effective and cost-saving compared to RPV/TDF/FTC from Russian vital and essential drugs list perspective.